Status of the Tana/Teno River salmon populations in 2025 : Report from the Tana/Teno Monitoring and Research Group - Erkinaro, Jaakko; Orell, Panu; Falkegård, Morten; Foldvik, Anders (Tana Monitoring and Research Group, 2026)
This report is the ninth status assessment of the re-established Tana/Teno Monitoring and Research Group (MRG) after the 2017 agreement between Norway and Finland. After a summary of salmon monitoring time series in Tana/Teno, we present an updated status assessment of fourteen stocks/areas of the Tana/Teno river system. All stocks were evaluated in terms of a management target defined as a 75 % probability that the spawning target has been met over the last four years. A scale of four years has been chosen to dampen the effect of annual variation on the status. Assessing the stock status is answering the question about how well a salmon stock is doing, how many salmon were left at the spawning grounds and how many should there have been. The question about how many salmon should spawn has been addressed by the defined spawning targets for the different populations (Falkegård et al. 2014). The unprecedented situation in 2021-2025, when a total moratorium of salmon fisheries was put in place both in the Teno/Tana river system and in large areas in Tanafjord and in adjacent coastal areas, meant that in contrast to the several alternative ways of estimating the spawning stock used in earlier years (Anon. 2020), only direct counts of ascending and spawning salmon were used in the assessments in 2021-2025 because of the absence of salmon catches.
Keywords: exploitation; fisheries management; management targets; mixed-stock fishery; monitoring; overexploitation; pre-fishery abundance; Salmo salar; spawning targets; status assessment; status evaluation; stock recovery; stock status